Experimental investigations on the performance of a thermo-mechanical refrigeration system utilizing ultra-low temperature waste heat sources - Ahmad K. Sleiti (14778229) (2023)
Experimental studies that investigate the utilization of ultra-low temperature (between 48 °C and 120 °C) waste heat, which forms 25 % of the global unrecovered waste heat, to drive thermal cooling systems are rare. Thus, this study fills a significant gap in the literature by (i) experimentally evaluating the performance of a new full-scale thermo-mechanical refrigeration (TMR) system at ultra-low temperatures ranging from 50 °C to 85 °C, (ii) characterizing its operation with different commercial refrigerants, and (iii) identifying optimal operating conditions and working fluids for the investigated TMR system. An organic Rankine cycle (ORC), vapor compression cycle (VCC), and expander-compressor unit (ECU) make up the TMR system. To ensure its efficient operation, flexibility, and reliability, a full-scale ECU-based TMR system with a design capacity of 1 kW at a heat source temperature of 85 °C is built and put through a series of tests. Furthermore, the TMR system is tested with different commercial refrigerants (R134a, R410A, R407C) over a wide range of operating conditions of the power loop. The results reveal that the ECU-based TMR system can work with ultra-low temperatures of 65 °C with an energy efficiency of 5.92 % and COP of 2.36, for the ORC and VCC, respectively. At a heat source temperature of 85 °C, a condenser water temperature of 15 °C, and an evaporator water temperature of 33 °C, the energy efficiency of the ORC and COP of the VCC are increased to 9.85 % and 3.99, respectively. For the cooling quality, the TMR system shows a minimum evaporator temperature of −10 °C using R134a in both the power and cooling loop, which is improved to lower than −20 °C by using R407C in the cooling loop. The results presented herein will be beneficial to the development, design, and optimization of refrigeration and power systems that utilize low-temperature waste heat. Other Information Published in: Alexandria Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.aej.2023.03.083